Analysis of Concrete with Different Ratio of Fiber (International Journal of Innovative Research in Engineering & Management, 2022)
There is no denying fiber reinforced  concrete's (FRC) value in a variety of civil engineering  applications. A wide variety of applications, including slabs  on grade, architectural panels, precast goods, offshore  buildings, structures in seismic zones, thin and thick repairs,  crash barriers, footings, hydraulic structures, and many more,  have successfully used fiber reinforced concrete to date. As  a practical means of enhancing concrete's performance, Fiber  Reinforced Concrete (FRC) is gaining popularity. Now,  fibers are being specified for use in concrete slabs, pads,  loading docks, thin unbonded overlays, tunnels, bridge  decks, and pavements. These applications of fiber-reinforced  concrete are getting more and more well-liked and function  exceptionally well. Concrete with fibrous reinforcement, or  fiber-reinforced concrete (FRC), has a higher structural  integrity. Short, isolated fibers that are evenly spaced out are  present.
Keywords: Steel Fiber Reinforced Concrete; tensile strength; compressive strength